Modified early warning score (MEWS) identifies clinical deterioration prior to development of unexpected acute pulmonary oedema. (18th April 2012) - Worton, SA; Higgins, L; Stephen, G; Gillham, GC
Abstract : Introduction: Pulmonary oedema, which historically accounted for 25% of toxaemia-related deaths, 1 is now an uncommon cause of maternal death due to implementation of policies for managing severe pre-eclampsia (PE).2 Case History: A 20year old primigravida was admitted at 35weeks gestation with hypertension (140/85), proteinuria (PCR 254) and normal blood results. Whilst fasted and not receiving intravenous fluids, elevated MEWS developed (MEWS=6; hypertension (145/88); tachycardia (112); tachypnoea (20)). The patient was asymptomatic and full clinical examination and an arterial blood gas were normal. She was transferred to the Delivery Unit for HDU-level care in accordance with local protocols. MEWS rapidly escalated (MEWS=9) and breathing deteriorated. Acute pulmonary oedema was diagnosed and treated by the multidisciplinary team. Liveborn twins were delivered by caesarean section. Postnatal echocardiogram was normal. Discussion: Acute pulmonary oedema developed rapidly despite clinically mild PE not qualifying for severe PET protocols. Recognised associations with pulmonary oedema were not present; post-partum, pre-existing hypertension, increased maternal age, parity and IV fluid replacement1 . The latest Confidential Enquiry into Maternal Deaths emphasised the importance of MEWS to recognise critically ill women at risk of complications and prevent deterioration3. In this case, HDU escalation in response to MEWS undoubtedly contributed to rapid diagnosis and management. Conclusion: Acute pulmonary oedema is an unpredictable, life-threatening complication of PE which can develop rapidly in young healthy women with clinically mild PE. MEWS algorithms can appropriately identify patients at risk of severe, unexpected complications facilitating the prompt management necessary to secure good outcomes for mother and baby.